2008
DOI: 10.1111/j.1399-0012.2008.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved renal function after kidney transplantation is associated with heme oxygenase‐1 polymorphism

Abstract: Heme oxygenase-1 (HO-1) has a microsatellite polymorphism based on the number of guanosine-thymidine nucleotide repeats (GT) repeats that regulates expression levels and could have an impact on organ survival post-injury. We correlated HO-1 polymorphism with renal graft function. The HO-1 gene was sequenced (N = 181), and the allelic repeats were divided into subclasses: short repeats (S) (<27 repeats) and long repeats (L) (>/=27 repeats). A total of 47.5% of the donors carried the S allele. The allograft func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
15
0
4
Order By: Relevance
“…Therefore, we may postulate that myeloid HO-1 expression induced by hemin requires a critical level to be effective and that this minimal threshold in HO-1 expression was not reached in LT. By inference, the length polymorphism of guanosine thymidine dinucleotide (GT) n repeats in the promoter region of Hmox1 was associated with lower HO-1 activity 55 , mimicking the effect of a hypomorphic allele. Interestingly, longer (GT) n repeats in the Hmox1 promoter were associated with the occurrence of CKD and decreased renal function after cardiac surgery or kidney transplantation in humans 11, 5658 . Also, it has been largely reported that hemin preconditioning significantly mitigates IRI-induced AKI 14, 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we may postulate that myeloid HO-1 expression induced by hemin requires a critical level to be effective and that this minimal threshold in HO-1 expression was not reached in LT. By inference, the length polymorphism of guanosine thymidine dinucleotide (GT) n repeats in the promoter region of Hmox1 was associated with lower HO-1 activity 55 , mimicking the effect of a hypomorphic allele. Interestingly, longer (GT) n repeats in the Hmox1 promoter were associated with the occurrence of CKD and decreased renal function after cardiac surgery or kidney transplantation in humans 11, 5658 . Also, it has been largely reported that hemin preconditioning significantly mitigates IRI-induced AKI 14, 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Donor GT-repeat length was more important for renal function. Donors containing at least one S allele demonstrated better function over a 3-year follow-up period (107). HO is important for renal allograft function and survival, representing an avenue for therapeutic intervention.…”
Section: Interstitial Renal Diseasementioning
confidence: 95%
“…Long polymorphisms, defined as greater than 25-27 repeats (L allele), in this region are associated with lower inducibility of HO-1 and increased risk of disease (14,27,30,107,148). Significant correlation with disease was identified in the settings of renal transplantation, diabetic kidney disease, CKD progression, AV fistula failure, and others (30,76,81,107,148). Recent evidence demonstrated microRNAs are involved in the regulation of human HO-1 expression in vitro (15).…”
Section: Fig 3 Ho Enzymatic Reactionmentioning
confidence: 99%
“…Four SNPs within the same gene, tested in a single center study, were only significantly associated with time to rejection in preliminary analysis before correction for multiple testing [25]. One study found statistically improved allograft function up to 3 years after transplantation in patients receiving kidneys from donors as well as recipients with an HO-1 S allele [6]. …”
Section: Long-term Allograft Dysfunction and Mortalitymentioning
confidence: 99%
“…Lack of association was also seen in two studies using the (GT) n repeat. However, one set the cutoff at 25 instead of 27 GT repeats [5], and the other was small with 181 patients [6]. …”
Section: Delayed Graft Functionmentioning
confidence: 99%